Reading authentic texts transforms reality - Albarracin Gómez, Adriana (Rastros Rostros, 2002)
The act of reading is a dynamic event where the reader enters into a direct relationship with the text and tries to "immerse himself in it" to find its meaning. In order to do so, the reader uses various clues such as: drawings, typefaces, letter sizes, text silhouettes, known words, punctuation and other significant marks. In other words, the act of reading is to construct meaning between the text and me.